Cyberattack on the NHLS Network: Highlighting the crucial role of laboratory medicine - Tahir S. Pillay (Journal of the Colleges of Medicine of South Africa)
The ransomware cyberattack on the National Health Laboratory Service (NHLS) network highlighted the indispensable role of laboratory medicine in the healthcare system. This incident severely disrupted the processing and release of patient samples, underscoring the critical yet often underappreciated contributions of laboratory medicine. Laboratory professionals operate behind the scenes, providing data crucial for medical decisions, yet they frequently face challenges such as resource allocation, limited public awareness, and professional recognition. In order to address the ‘Cinderella specialty’ perception of laboratory medicine, it is essential to enhance visibility, education, and resource allocation. Governments and politicians can play a pivotal role in this transformation by increasing funding for laboratory infrastructure and technology, reinforcing laboratory medicine in medical curricula, launching public awareness campaigns, and supporting workforce development. In addition, fostering innovation through research grants and policy advocacy can further elevate the status of laboratory medicine. By recognising and addressing these issues, the healthcare system can ensure that the contributions of laboratory professionals are fully appreciated, leading to improved patient care and health outcomes.